KEKUATAN PERLEKATAN GESER ANTARA BAHAN PEREKAT RESIN KOMPOSIT DAN GELAS IONOMER HIBRID PADA PERAWATAN ORTODONSI DENGAN SISTEM PERLEKATAN LANGSUNG - Marisnawati, Amik; Sutjiati, Rina (STOMATOGNATIC- Jurnal Kedokteran Gigi, 2012)
Measurement of shear bond strength is one that a material meets the eligibility requirements and testing the strength of attachment of the most common. This experimental research laboratories using 20 first premolars were divided into two groups, G1: 10 teeth are attached to the resin composite, G2: 10 teeth are attached to the glass ionomer hybrid. All of the teeth soaked in distilled water, and then stored in the incubator (37C) for 24 hours. Measurement of shear bond strength used the tool `s Digital System Torsee Universal Testing Machine. The data were analyzed using t-test. These results indicate shear bond strength of resin composite was higher when compared to glass ionomer hybrid.